Investigating the relationship between environmental literacy and mathematical literacy toward computer self-efficacy in secondary school - Ahmad Rozikin; Suherman Suherman; Farida Farida; Riccardo Tasca (CV. FOUNDAE, 2024)
Background: The twenty-first century has been characterised by remarkable advances in technology, information, and communication, underscoring the importance of environmental and mathematical literacy in navigating this digital age.Aim: The study aims to investigate the influence of environmental and mathematical literacy on computer self-efficacy.Method: This study employed a quantitative methodology within a correlational research design, with a total of 47 secondary school students participating by random sampling. Regression analysis was used to analyse the data, revealing insightful findings on the relationship between environmental and mathematical literacy and computer self-efficacy.Results: After conducting the prerequisite checks for the regression test, it was determined that the feasibility of testing the hypothesis by the data, particularly through the regression test. In this study, the results showed that the relationship between environmental literacy and mathematical literacy with computer self-efficacy abilities is particularly significant. In fact, the study found that the combined influence of environmental and mathematical literacy on computer self-efficacy is stronger than its individual effects, suggesting a synergistic relationship between these types of literacy. Furthermore, mathematical literacy emerged with the highest average score of 62.070, followed by environmental literacy and computer self-efficacy abilities, which received average scores of 54.875 and 55.953, respectively.Conclusion: In summary, the study underscores the significant positive impact on the relationship between environmental and mathematical literacy on computer self-efficacy among secondary school students. By improving environmental and mathematical literacy, educators and researchers can empower students with the skills and competencies necessary to navigate the digital landscape with confidence and proficiency.